Road Safety Awareness: Australian Road Crash Case Study - Jessica, Jessica; Sunardi Oetama, Raymond (Publisher Cv. Inara, 2023)
Road transportation accidents are a significant public health and safety issue worldwide. In Australia, regarding transport-related deaths, the age-standardized rate was higher in one specific year compared to the preceding year. This study aims to make visualization of crash data in Australia play a crucial role in understanding the country's current state of road safety and developing strategies to improve it. Data visualization techniques are essential in understanding and addressing road safety in Australia. New South Wales has the highest number of accidents in Australia, with 16,293 cases. Accidents in New South Wales are projected to decline gradually over the next three years. The peak time for accidents is 3 PM on weekdays, with males being more involved than females. Drivers are the most involved road users in accidents. Implementing targeted road safety initiatives, gender-specific awareness campaigns, and driver safety programs can help reduce accidents in New South Wales and create a safer environment for all road users. By analyzing accident data visually, patterns and trends can be identified, leading to targeted interventions and improved safety measures to reduce the number of accidents and fatalities on the roads.